Aging Influence on Chemical Properties of Palm Oil Mill Sludge Modified Asphalt Binder - Norazni, Nur Shazwina Asmira; Mohd Kamaruddin, Nurul Hidayah (Recent Trends in Civil Engineering and Built Environment, 2024)
The usage of asphalt binder as a primary component of the surface course required a high cost although used in a lower percentage besides it is a non-renewable substance. The present binder materials, on the other hand, have a problem with bitumen ageing. As a result, a lot of research is focusing on changing the asphalt binder to reduce the reliance on this non-renewable substance and its effect to the chemical composition of the asphalt binder changes owing to oxidation. This study presents the physical properties of unmodified and modified asphalt binder follows with quantify the effect of aging on chemical properties of palm oil mill sludge (POMS) modified asphalt binder. The PEN 60/70 was used in this study as a control sample while percentage of POMS varies from 0% to 5%. Three tests were conducted to investigate the properties of unmodified and modified asphalt binder, these include penetration, softening point and Fourier Transform Infrared Spectroscopy (FTIR) test. The findings showed that the POMS modified asphalt binder is soften throughout the addition of percent. It indicates that the POMS modified asphalt binder has a high temperature susceptibility. The effect of aging to the POMS modified asphalt binder also has proved to be delayed throughout the addition of percent. Future study on the rheological characteristic can be made in determining the performance of asphalt binder under certain range temperature.